Para uma nova interpretação do corporar: o corpo à luz da transcendência do Dasein - Pessoa, Rodrigo Rizerio De Almeida E [UNIFESP] (2019)
The work aims to locate the place of the body in the existential analytic of Martin Heidegger, author often accused, mainly by the French philosophers, to have neglected this problem in its analysis of the human existence. However, even though very little has been said about corporeality in the context of 1927 analytics, the text of the Zollikon Seminars of a few decades later allows one to visualize what would be the place of the corporeal in the being-in-the-world structure of being, illuminating even the text of 1927, in which one can already find, despite his silence on the body, traces of an unrealized corpora. The research further explains that Heidegger's analytic allows us to visualize the being of man beyond the dualist reading for whom the human is composed of interdependent parts, that is, body and soul, or living organism and mental representations, in which what is mutant, unstable, corruptible, that is, the body, has always been understood as lesser or of lesser theoretical dignity than that of soul or rationality. In the light of analytics, on the contrary, the being of man is aimed according to a unitary and non-fragmentary conception, the totality of which is not the result of mere summation of parts, but consists of essential constitutive moments, among which, however, body. According to this one and undivided reading of the totality of existence, the body comes to the surface not as the mere opposite of the soul, since there is no more place for any opposition or duality. The being of man does not allow himself to be seen through his living organism or his mental representations, but as a third thing between these two dichotomous poles. Thus conceiving man, the body, on the other hand, does not allow itself to be seen among the ontic-material characters of being-there, since, as Heidegger himself said it, the human body is something of another in relation to the animal organism, nor among the ontological-formal characters, for in this case the being-there would be something like a floating vapor or phantom, without worldly concreteness. In this way the body must be seen as a third thing or, in the light of the image that comes to us from Rosa's literature, as the third margin between what is ontological and what is ontological in being-there, as a phenomenon therefore.